(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The pathogenesis of SARS-CoV-2 is not fully understood, and currently there is currently no definitive drug or treatment against it. So, the drugs used to treat SARS-CoV-2 are mainly based on their effectiveness on previous species of coronaviruses. This review aimed to evaluate the studies performed on the use of the available drugs in the treatment of Covid-19 since the onset of this disease.Method: Comprehensive search strategy was conducted in the following databases: PubMed, Web of Science ISI and Scopus, Psycinfo, Google Scholar, and national databases, including Scientific Information Database SID and MagIran from inception of Covid-19 to June 2022. Studies that reported the effect of different drugs in treatment of Covid-19 patients were included.Results: 38 studies 114,552 participants were included in this systematic review study on used drug treatment of patients with Covid-19 including Remdesivir, HCQ & Chloroquine, Favipiravir, Molnupiravir, Arbidol, Kaletra, Oseltamivir, IVIG & Interferon.Conclusions: Remdesivir, HCQ & Chloroquine, Favipiravir, Molnupiravir, Arbidol, Kaletra, Oseltamivir, IVIG & Interferon are the most commonly used drugs in treatment of Covid-19. Although these drugs may be effective in improving the condition of Covid-19 patients in the inflammatory phase, the confirmation of their use requires more extensive clinical research.